Aktivitas Antioksidan dan Inhibitor Enzim Tirosinase Ekstrak Daun Jeruk Manis (Citrus sinensis L.) - Saragih, Runitasari; Fachrial, Edy; Pranita Simanjuntak, Nerly Juli (Herbal Medicine Journal, 2026)
Sweet orange leaves (Citrus sinensis L.) are a potential source of bioactive compounds that can be developed as natural antioxidants and tyrosinase inhibitors for the prevention of premature skin aging and hyperpigmentation. This study aimed to evaluate the phytochemical constituents, antioxidant activity, and tyrosinase inhibitory potential of the ethanol extract of sweet orange leaves. Extraction was carried out using ultrasonic-assisted extraction with 70% ethanol as the solvent. Phytochemical screening revealed the presence of flavonoids, tannins, alkaloids, and steroids, while saponins were not detected. Antioxidant activity was evaluated using the DPPH radical scavenging method at concentrations of 200–500 ppm and showed a concentration-dependent increase in inhibition, with values of 76.46% (200 ppm), 78.61% (300 ppm), 82.32% (400 ppm), and 84.43% (500 ppm), indicating strong antioxidant activity. Tyrosinase inhibition was assessed using L-DOPA as the substrate and demonstrated inhibition percentages of 51.13% and 51.01%, indicating good inhibitory activity. Based on these findings, thethanol extract of sweet orange leaves exhibits promising antioxidant and tyrosinase inhibitory properties and may be further developed for pharmaceutical and cosmetic applications, particularly as natural anti-aging and antihyperpigmentation agents.